Training for self-employment and active citizenship to achieve life satisfaction (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2018)
Forecasting the future of the world of work is difficult, dependent on multiple factors that are themselves unpredictable. The world of work is prone to transit from predominantly employee-based economies to entrepreneurial economies, involving the change in the work habits of individuals. The practical question arises: Are future generations ready to be entrepreneurial, and how to promote entrepreneurial education in the higher educational settings? The article below, beyond the purely economic rationale behind entrepreneurial education, tries to enumerate and examine the societal and psycho-social outcomes of self-employment such as life satisfaction and subjective well-being.